The Need to Improve the Quality of Social Activity in the Health of Young People Through Physical Education and Sports - Saidova Aziza Yakubovn; Erkaev Eldor Abdukarimovich (Genius Journals, 2022)
This article is based on the need to increase the social activity of young people and the fact that increasing the social activity of young people is a purposeful organizational and pedagogical process, in which the need to improve and enrich the qualities of social activity is formed in young people.
Keywords: Education; upbringing; harmoniously; education